Strategical alignement of human capital management in mining metallurgy - Aybar Vargas, Carlos Modesto (2013)
This work, in synthesis, is about the exercise of good corporate management practice. The systematic nature of administration, alignment, strategy and skills in the metal mining sector in peru, influence of the Resource and Capacity development theory. We also deal with the value chain, competitive advantages, strategies and skills in the metal mining activity and mining strata. From the development of these points, we set up as conclusions that all formal, legal or illegal strata coexist somehow because the legal ones can export all production. On the other hand, it is required a strategy, promotion, planning and specialized professional leadership in this industry. At the same time, it is required that the government support all this effort and the centers of technical and vocational training in geology, mining, metallurgy, chemistry and related competences define and design formation competence to provide the specialized human capital sector.